2018
DOI: 10.1364/josab.35.002096
|View full text |Cite
|
Sign up to set email alerts
|

Upconversion single-photon detectors based on integrated periodically poled lithium niobate waveguides [Invited]

Abstract: We demonstrate up-conversion single-photon detectors based on integrated periodically poled lithium niobate waveguides, which incorporate two mode filters and a directional coupler. The two mode filters are optimized for the fiber-waveguide coupling efficiencies for 1550 nm and 1950 nm respectively while the directional coupler plays the role of wavelength combiner, making the overall system portable and low-cost. The two wavelengths pump each other in our detection system. We achieve detection efficiencies of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 37 publications
(50 reference statements)
0
7
0
2
Order By: Relevance
“…With this setup, our up-conversion receiver can work only for short-distance QKD, below 6 dB channel loss, as shown in Figure 5f). Nonetheless, state-of-the art systems for up-conversion detectors of single-photon signals in the C band, have demonstrated a very high overall efficiency above 30%, with a dark count rate as low as 100 Hz, thus enabling quantum communication up to 45 dB of channel loss [39][40][41]. Furthermore, it is important to notice that although we have used a bulky and custom home-made system (which requires the pre-alignment of the free-space silicon detector), the nonlinear crystal could be integrated in photonic platforms for a more efficient and stable solution [42].…”
Section: Discussionmentioning
confidence: 99%
“…With this setup, our up-conversion receiver can work only for short-distance QKD, below 6 dB channel loss, as shown in Figure 5f). Nonetheless, state-of-the art systems for up-conversion detectors of single-photon signals in the C band, have demonstrated a very high overall efficiency above 30%, with a dark count rate as low as 100 Hz, thus enabling quantum communication up to 45 dB of channel loss [39][40][41]. Furthermore, it is important to notice that although we have used a bulky and custom home-made system (which requires the pre-alignment of the free-space silicon detector), the nonlinear crystal could be integrated in photonic platforms for a more efficient and stable solution [42].…”
Section: Discussionmentioning
confidence: 99%
“…The upconverted signal is detected by visible-near infrared detectors. In the past decade year, there are many researches about frequency upconversion [4], [10]- [13]. Taking advantage of high peak power of pulse laser, the upconversion efficiency of 64% has been achieved with the average pump power of 28.7mW at 17.9M Hz within the pulse duration of 5.3ps [14].…”
Section: Introductionmentioning
confidence: 99%
“…A total detection efficiency of ∼ 3.7% was achieved with a quite low noise probability per pulse of 0.0002. In 2018, Ma et al [19] used 1550 nm and 1950 nm two wavelengths pump each other to yield 864 nm by using PPLN waveguide with a conversion efficiencies of ∼ 28% and ∼ 27% respectively. In 2018, Wright et al [20] reported two-way photonic interface for linking 422 nm to the telecom C-band, and achieved up-conversion (down-conversion) at singlephoton level with conversion efficiency of ∼ 9.4% (∼ 1.1%), and SNR of ∼ 39.4 (∼ 108).…”
Section: Introductionmentioning
confidence: 99%